The neck of Barosaurus was not only longer but also wider than those of Diplodocus and other diplodocines - Taylor, Michael P; Wedel, Mathew J (PeerJ PrePrints, 2013)
Barosaurus is a diplodocid sauropod from the Upper Jurassic Morrison Formation of the western United States, and is known for its very long neck. It is related to the sympatric Diplodocus, and often thought of as more or less identical except with a longer neck. The holotype YPM 429 includes three and a half posterior cervical vertebrae, somewhat distorted and damaged, which are nevertheless very distinctive and quite different from those of Diplodocus. The cervicals of the better known and more complete referred Barosaurus specimen AMNH 6341 show the same characteristic features as the holotype, though not to the same extent: transversely broad but anteroposteriorly short zygapophyseal facets; prezygapophyses carried on broad, squared-off rami; zygapophyses shifted forward relative to the centrum; diapophyses, parapophyses and neural spines shifted backwards; and broad diapophyseal “wings”. These features form a single functional complex, enabling great lateral ﬂexibility, but restricting vertical ﬂexibility. This may indicate that Barosaurus used a different feeding style from other sauropods perhaps sweeping out long arcs at ground level. The Morrison Formation contains at least nine diplodocid species in six to eight genera whose relationships are not yet fully understood, but Barosaurus remains distinct from its relatives.
Keywords: Barosaurus; neck; Diplodocus; dinosaur; sauropod; cervical vertebrae